Leech therapy: a non-surgical management for varicose vein - Iqbal, Arshid; Jan, Afroza; Rashid, Adil; Anayat, Syed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Varicosity refers to multiple, dilated, tortuous, and elongated veins that have permanently lost their valvular efficiency, such as haemorrhoids, varicocele, and esophageal varices. Varicose veins are twisted and enlarged veins that are commonly found in the legs. When veins become varicose, the valves stop working properly, allowing blood to flow backwards and the veins to engorge. Varicose veins are most common in the superficial veins of the legs, with the veins engorging and ulcerating as a result of standing under high pressure. The purpose of this case series is to evaluate the efficacy of Hirudotherapy in the treatment of varicose veins in the lower legs. Hirudotherapy was carried out scientifically by employing appropriate hygienic measures, and 8 to 10 leeches were used locally to suck the blood and transmit important bioactive enzymes that could aid in the treatment of varicose veins of the lower legs. Hirudotherapy was given every ten days for 60 days, and patients were monitored for a year. Leech therapy was found to significantly reduce venous engorgement by resolving edema, inflammation, and venous congestion.